The Surgical Scheduling Problem: Current Research and Future Opportunities - May, Jerrold H.; Spangler, William E.; Strum, David P.; Vargas, Luis G. (Production and Operations Management, 2011)
This paper reviews the general problem of surgical scheduling. We organize the literature based on the time frame or planning horizon of the schedule into six categories: capacity planning, process reengineering/redesign, the surgical services portfolio, procedure duration estimation, schedule construction, and schedule execution, monitoring, and control. We survey past work and suggest topics for potential future research in each of those areas.